The effects of primary and recurrent pediatric urological surgeries on parental anxiety levels. Issue 5 (October 2020) - Selvi, Ismail; Hajiyev, Perviz; Ekberli, Gunay; Baklacı, Utku; Soygur, Tarkan; Burgu, Berk
Summary: Introduction: Invasive diagnostic and therapeutic procedures in pediatric urology may generally cause distress and pain in children. As a result, it may have a negative effect on adult and child behaviors. The anxiety, depression levels or distress and fear status caused by recurrent diseases or repetitive medical interventions in adult patients or the parents of pediatric patients have been investigated previously. Objective: To the best of our knowledge, we have not found a study evaluating the effects of primary or recurrent pediatric urological operations on parental anxiety. Our main aim was to compare the effects of primary and repetitive pediatric urological surgeries on the anxiety levels of both mothers and fathers. We also aimed to investigate the effects of other factors related to parents and children on parental anxiety. Design: A total of 163 patients under 14 years old who had undergone primary or recurrent pediatric urological operations and also their parents were included in a prospective, cross-sectional study. Demographic and clinical data of the patients and their parents were recorded. Before the surgeries, the Children's Fear Scale was applied to all patients over 3 years old and the State-Trait Anxiety Inventory was applied to all parents. The participants were divided into two main groups: primary surgery group (n:84) and recurrent surgery group (n:79). A subgroup analysis was performed according to surgery type (day surgery, minor surgery and major surgery). Results: We found that repetitive surgeries, higher fear scores of children, parents' being younger, having low education level, not having enough information about the surgeries and presence of someone in the immediate vicinity who previously experienced the same surgery increased parental anxiety levels. Day surgeries did not affect fathers' state anxiety levels as much as minor and major surgeries, whereas mothers' state anxiety levels were higher than fathers' regardless of the surgery type. Children's fear level was not affected by child age, gender, surgery type or previous history of surgery. Discussion: The majority of studies in the literature show no significant difference in terms of pain and fear levels in pediatric patients undergoing repeated diagnostic interventions but there are contradictory results about parental anxiety levels. There is also a lack of studies on the effects of recurrent surgeries. Conclusion: According to our findings, repetitive surgeries and presence of someone who previously experienced the same surgery are the most significant predictive factors increasing parental anxiety levels. Summary Table Predictive factors for the development of mothers' and fathers' state anxiety. Summary Table Multivariate analysis for mothers' state anxiety Multivariate analysis for fathers' state anxiety OR %95 CI p OR %95 CI p Lower Upper Lower Upper Surgical status (Recurrent vs. primer) 17.892 6.993 45.781 <0.001∗ 5.930 2.080 7.952 0.035∗ Surgery type (major/minor vs. day surgery) 1.854 1.004 3.421 0.048∗ The number of re-operations in recurrent cases 3.267 2.124 11.035 0.004∗ 2.025 1.456 4.123 0.041∗ Time to recurrent operation 1.488 0.826 2.680 0.036∗ 1.018 0.756 1.953 0.042∗ The mother's age 1.025 0.975 1.237 0.003∗ The father's age 1.019 0.678 2.025 0.013∗ The mother's educational level 1.125 0.892 1.986 0.029∗ The father's educational level 1.192 0.753 1.861 0.021∗ The mother's working status 1.458 1.027 4.239 0.024∗ Presence of siblings or someone who has had the same surgery in the immediate vicinity 4.457 2.147 8.157 0.032∗ 2.774 1.870 5.190 0.001∗ The Children's Fear Scale score 1.980 0.826 2.167 0.023∗ 1.743 1.049 2.896 0.032∗ The trait anxiety status of the mother 1.291 0.979 4.487 0.030∗ The trait anxiety status of the father 1.201 1.182 1.411 <0.001∗ The mothers' thinking whether they have enough information about the surgery 1.240 0.786 2.157 0.024∗ The fathers' thinking whether they have enough information about the surgery 1.147 0.623 1.840 0.031∗ ∗p < 0.05 Asterisk (∗) indicates statistical significance. Logistic regression .